From neoplastic neural development to gene therapy of brain tumors -IGF-I antisense and triple helix approaches - Trojan, Jerzy (Komitet Biotechnologii PAN, 2003)
IGF-I, insulin - like growth factor I, seems to play a major role in the normal and tumoral development of the nervous system. Glioblastoma is the mostfrequent brain tumor in man and is usually fatal. Both human and rat gliomacells express high amounts of lGF-1. When rat glioma cells are transfected withvectors expressing either IGF-I antisense RNA or inducing IGF RNA - DNA triplehelix, the synthesis of IGF-1 was stopped on translation or transcription levels,respectively. Down-regulation in the expression of IGF-I coincides with the reappearance of B-7 and MHC class 1 antigens at the surface of transfected cells.When injected subcutaneously, the transfected cancer cells initiate an immunereaction involving CD8-F lymphocytes, followed by tumor regression. The«anti-gene» strategy for clinical therapy of glioblastoma, and other tumors expressing IGF-I such hepatomas were introduced in University Hospitals of Cleveland (USA), Shanghai (China), Krakow and Bydgoszcz (Poland).
Keywords: biotechnologia